2019
DOI: 10.12984/egeefd.488612
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının Hayat Boyu Öğrenme ve Yetişkin Eğitimi Dersine Yönelik Görüşleri

Abstract: Öz Anahtar Sözcükler 21. yüzyılda genç nesilleri hayata hazırlamak ve bir ömür boyu kişisel, sosyal ve psikolojik açıdan gelişimsel gereksinimlerini karşılayabilmelerini desteklemek için hayat boyu öğrenme ve yetişkin eğitimi konusunda bilinç oluşturmak bir gereklilik taşımaktadır. Bu düşünceler temelinde YÖK, eğitim fakülteleri için hazırladığı yeni lisans programlarında Yetişkin Eğitimi ve Hayat Boyu Öğrenme isimli bir seçmeli ders oluşturmuştur. Bu çalışmanın amacı öğretmen adaylarının söz konusu derse yöne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Moreover, when the relevant literature is examined, it is seen that there is a very little research on high school students' or adolescents' lifelong learning tendencies (Asiloğulları, 2020;Brooks, 2006;Güzel, 2017;Kalçık, 2017;Semerci & Kalçık, 2017;Ünal & Kalçık, 2017). The studies conducted in the field of lifelong learning tendency were found to be largely focused on teachers (Gökyer, 2019;Tanatar & Alpaydın, 2019), pre-service teachers (İlic & Haseski, 2019;Yenice & Tunç, 2019), university students (Arslan et al, 2019;Denat et al, 2016) and trainees in different institutions (Adabaş, 2019;Akyol et al, 2018) while high school students or adolescents were not much preferred in these studies.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, when the relevant literature is examined, it is seen that there is a very little research on high school students' or adolescents' lifelong learning tendencies (Asiloğulları, 2020;Brooks, 2006;Güzel, 2017;Kalçık, 2017;Semerci & Kalçık, 2017;Ünal & Kalçık, 2017). The studies conducted in the field of lifelong learning tendency were found to be largely focused on teachers (Gökyer, 2019;Tanatar & Alpaydın, 2019), pre-service teachers (İlic & Haseski, 2019;Yenice & Tunç, 2019), university students (Arslan et al, 2019;Denat et al, 2016) and trainees in different institutions (Adabaş, 2019;Akyol et al, 2018) while high school students or adolescents were not much preferred in these studies.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…When national (Adabaş, 2019;Akyol, Başaran, & Yeşilbaş, 2018) and international research (Castleberry, Ward, & Stein, 2019;Sullivan, Fulcher-Rood, Kruger, Sipley, & van-Putten, 2019) on lifelong learning are reviewed, it is seen that these studies largely focus on the investigation of lifelong learning skills in adults. There are many national studies investigating lifelong learning tendencies of university students (Arslan, Bıçakçıgil-Özsoy, & Aslan, 2019;Denat, Dikmen, Filiz, & Başaran, 2016;Yıldız-Durak & Sarıtepeci, 2019), teachers (Aydoğan, 2019;Gökyer, 2019;Tanatar & Alpaydın, 2019), pre-service teachers (Bulaç & Kurt, 2019;İlic & Haseski, 2019;Yenice & Tunç, 2019) and trainees in different institutions (Adabaş, 2019;Akyol et al, 2018). However, the number of studies conducted to determine young individuals' lifelong learning tendencies is very small in both national literature (Asiloğulları, 2020;Güzel, 2017) and international literature (Brooks, 2006).…”
Section: Research Problemmentioning
confidence: 99%